A preliminary randomized controlled study of the PEERS® program for Taiwanese autistic adolescents: The effectiveness on reducing school bullying and enhancing social function - Hsiao, Mei-Ni; Chien, Yi-Ling; Tai, Yueh-Ming; Chen, Heng-Man; Shih, Hsien-Hsueh; Chen, Li-Wei; Chen, Yu-Ying; Soong, Wei-Tsuen; Chiu, Yen-Nan; Tsai, Wen-Che; Laugeson, Elizabeth; Tseng, Mei-Hui; et al. (Autism research, 2024)
Individuals with autism spectrum disorder (ASD) often experience lifelong social communication challenges and are more vulnerable to school bullying. Addressing their social difficulties and school bullying requires evidence-based interventions. PEERS® (Program for the Education and Enrichment of Relational Skills) was adapted and translated for Taiwanese adolescents. This randomized controlled study aimed to examine the effectiveness of the Taiwanese version of PEERS® in reducing school bullying and enhancing social function among autistic adolescents. Twenty-one autistic adolescents (mean age 14.29 ± 1.67 years; female n = 733.33%) were randomized to a treatment group (TG, n = 10) or a delayed treatment control group (DTG, n = 11). The outcome measures (school bullying, social challenges, social skills knowledge, and social skills performance) were assessed at baseline, post-treatment, and follow-up. The group and time interaction analyses revealed greater magnitudes of reduction in general school bullying (p < 0.001), victimization (p < 0.001), perpetration (p = 0.012), social challenges (p = 0.001), and peer conflicts (p < 0.001), and improvement in social knowledge (p < 0.001) in the TG group than the DTG group. The findings suggest that the PEERS® program tailored for Taiwanese adolescents is effective in reducing school bullying, decreasing social challenges, and enhancing social skills among autistic adolescents, with very large effect sizes (Cohen's d ranging from 1.19 to 2.88). Consequently, participation in the PEERS® program is recommended for adolescents with social difficulties to improve their social communication and interactions to offset school bullying and other social challenges related to adverse outcomes.